'Finding the needle in the haystack'- will natural products fit for purpose in the treatment of cryptosporidiosis? – A theoretical perspective. Issue 8 (24th May 2021) - Omolabi, Kehinde F.; Agoni, Clement; Olotu, Fisayo A.; Soliman, Mahmoud E.S.
ABSTRACT: The limitations that have inundated mainstream anticryptosporidials have necessitated the exploration of alternative approaches towards the design of novel anticryptosporidials with improved therapeutic activity. We virtually screened a dedicated library of 107, 000 natural compounds available in the ZINC database against Cryptosporidium parvum inosine monophosphate dehydrogenase-NAD + binding site. The top three compounds identified with the best complementarity to the Cp IMPDH-NAD + binding site included ZINC5225833, ZINC4258873, and ZINC3841381. Estimation of the total binding free energy using Molecular Mechanics Generalized Poisson Boltzmann Surface Area (MM/PBSA) method had the three compounds eliciting favourable binding free energies. ZINC3841381 had the best binding free energy of −58.43 kcal/mol followed by ZINC4258873 with −51.1 kcal/mol and ZINC5225833, −38.04 kcal/mol. The binding of the natural compounds to Cp IMPDH induced structural perturbations in the protein compared to the apo. We evaluated the compliance of the natural compounds to Lipinski's rule of 5 and other pharmacokinetic parameters. From this evaluation, the natural compounds are drug-likely but can still make do with some modifications to improve their therapeutic potentials. The results obtained from this study can serve as a preliminary background in the further experimental exploration of ZINC5225833, ZINC4258873, and ZINC3841381 as potential anticryptosporidials.